Challenges to cognitive bases for an especial motor skill at the regulation baseball pitching distance - Simons, J. P.; Wilson, J. M.; Wilson, G. J.; Theall, S. (Research Quarterly for Exercise and Sport, 2009)
We tested expert baseball pitchers for evidence of especial skills at the regulation pitching distance. Seven college pitchers threw indoors to a target placed at 60.5 feet (18.44 m) and four closer and four further distances away. Accuracy at the regulation distance was significantly better than predicted by regression on the nonregulation distances (p < .02), indicating an especial skill effect emerged despite the absence of normal contextual cues. Self-efficacy data failed to support confidence as a mediating factor in especial skill effect. We concluded that cognitive theories fail to fully account for the patterns of observed data, and therefore theoretical explanations of the especial skills must address noncognitive aspects of motor learning and control.